Peningkatan Kemampuan Keaksaraan Melalui Kegiatan Menjurnal (Penelitian Tindakan pada Siswa TK Islam Bina Insan Mandiri, Bekasi, 2016) - Wijaya, Purwani Kusumawati (STIT Al-Marhalah Al-Ulya Bekasi, 2018)
This research purposes is to obtain empirical data about jurnal writing activity in effort to improve student literacy ability. The method that used in this research is a action research. In this study, researcher act as an observer and classroom teacher as a collaborator. These action research, through four stages activities, which are planning, action, observing, dan reflecting. Action in this research was conducted in two cycles with 31 meetings. Sources of data in this study were students at TK Islam Bina Insan Mandiri. The collection of data is done through observation, interviews, and documentation study. The result showed that writing journal activity can improve student literacy ability, that average value on pre-cycle was 39,3%. Than increased to 65,9% in first cycle dan more increasing to 86,1% in the second cycle. It shows that the research minimal target as 71% has been achieving. The reaseach concludes that writing journal activity become one of good alternative method for improving student literacy ability